QUALITY IMPROVEMENT ON TRANSFORMATION GEOMETRY COURSE THROUGH THE IMPLEMENTATION RECIPROCAL TEACHING MODEL AT MATHEMATICS EDUCATION STUDY PROGRAM IN CHRISTIAN UNIVERSITY OF TENTENA - Natan Mentaruk (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2015)
The study aims at improving the coerse quality by implementing Reciprocal Teaching model to students of Mathematics Education Department in Christian University of Tentena of academic year 2012/2013. The course using Reciprocal Teaching model implements summarizing strategi, questions, clarifying and predicting. At this cours, students conducted those four strategies in a small group determined by the lecturer. The lecturer acted as the facilitator in this course.Based on the observation by the observer, the lecturer and students’ activities are in goog category; whereas, the result of final test of students is also in good category. Based on those findings, it is concluded that the course procedures of Transformation Geometry by implementing Reciprocal Teaching model are (1) students in group conducted summarizing which summarized the material of LKM, (2) students in group conducted questioning which arranged the questins and answers based on the material of LKM, (3) students in group conducted clarifying which clarified the summary, questions or answer from class presentation, (4) students in group conducted predicting which made prediction concerning Transformation geometry. The implementatin of Reciprocal Teaching model can improve the course and learning outcomes of students. The learning process of students improves from fair category to good category; whereas, students’ learning outcomes improve from 52,38% to 80,95%. Students’ response is stated as positive toward the learning activities which implemented Reciprocal Teaching model because 76% students gave positive response toward 97% of the aspects stated